Za jakých podmínek je pro firmu lukrativním společensky zodpovědné chování? - Jiří Hlaváček; Michal Hlaváček (Charles University in Prague, Institute of Economic Studies (IES), 2007)
– The theory 'corporate social responsibility' (CSR) is characterized in the paper. The paper expresses the authors' opinion, that CSR as a mere proclamation of necessity of the firms' ethic behavior does not enforce this into praxis. The internal economic motivation to CSR it is the necessary condition to firms to invest in CSR. The conditions for such motivation are than formulated.
Keywords: 330; corporate social responsibility; ethic firms' behavior; trust; credibility; economic motivation; Corporate Social Responsibility; Unternehmensethik; Glaubwürdigkeit; Firmenimage; Theorie